The Haitian Orthopaedic Residency Exchange Program. (August 2019) - Belding, Robert; Grabowski, Gregory; Williams, Kevin; Mobley, Kyle; Bray, Chris; Woolf, Shane; Jumelle, Patrick; Koon, David
Abstract : Background: After a devastating earthquake in Haiti in 2010, multiple South Carolinian orthopaedic teams, funded by the South Carolina Orthopedic Association (SCOA), developed an exchange program for Haitian residents. Methods: SCOA teams have sequentially logged their patient experiences since 2015 for a total of six updates per year. These logs were reviewed in detail to evaluate clinical results in terms of case volumes, cases performed, follow-up obtained, and complications. Results: Twenty-one orthopaedic attendings, 19 South Carolina orthopaedic residents, 22 Haitian orthopaedic residents, and 22 ancillary staff have rotated through Hospital Lumiere. The teams have seen over 2000 patients in the orthopaedic clinic and performed 554 surgeries, including 207 fractures (half of which being open), 24 nonunion and 7 malunion repairs, 15 lower extremity amputations, 27 hemiarthroplasties for femoral neck fractures, and 34 cases of chronic osteomyelitis. Discussion: The SCOA Foundation has developed a coordinated service for the musculoskeletal needs of the Haitian people while collaboratively elevating the standard of orthopaedic training in Haiti. We report a collaborative model that other US residency programs can use to impart beneficial changes not only in their home program, but also in training programs abroad.